The objects from elsewhere, here and over there : perceptions, practices and meanings of african objects - (:unkn) unknown (My University, 2012)
This research aims to analyze, through ethnographic inquiry, the phenomenon of qualification of the "African objects" as well as the personal and institutional problems that justify their appropriation and appreciation. Based on a field survey conducted in France and Mali, the study seeks to identify the spectrum of individual and collective practices that are organized around and with these productions. Europeans or Africans, amateurs, collectors, carvers, tourists and merchants, a multiplicity of individual actors, sometimes coming from areas totally strangers to each other, revolve around this object class and consider them from various perspectives. Based on a dynamic approach and on a historical viewpoint to draw a symmetrical anthropology of these objects - symmetry Africa/West, objects/people, expert/layperson - the goal is to build an observation framework which allows to respect the diversity of appropriation forms of these material productions. In other words, this work wants to analyze the physical, semantic or conceptual transformations which objects are subject for their circulation and because of their transit between geographical areas, national cultures and different economic worlds. The observation of socio-technical devices on which lean on the tastes, practices and worldviews of these actors allows to identify the stakes that unite them or divide them.
Keywords: African Research